A Qualitative Exploration of Food Literacy in International Schools in Egypt - Pugsley, Amy (AUC Knowledge Fountain, 2023)
Food literacy is an essential part of good physical and psychological health, however, food literacy is not a mandatory part of K-12 education in all schools. Many factors can influence food literacy levels including familial culture, socioeconomic status, and education levels. This research seeks to examine perceptions of food literacy in high school students and educators at two private American international schools located in Cairo, Egypt. Through the use of observations and interviews, the researcher used a qualitative approach to understand the self-perceptions of food literacy in students studying the American curriculum. The study revealed that students from high-socio-economic backgrounds need academic support to improve their food literacy levels. This study contributes to the educational research on food literacy and the importance of food literacy in the well-being of students.